An Effort to Disengage Mind-Wandering (The Integrated Study between Psychology and Sufism) - Erna Dwi Nugraini; Nurul Hikmah Sofyan (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2021)
Mind-wandering is a condition in which the mind is not focused on the task but wanders widely and spontaneously outside the topic of the task. This becomes a problem when someone is working on a task that requires full concentration, such as when a doctor performs an operation, a scientist conducts an experiment, or an entrepreneur presents a project plan in front of a client. This study aims to provide an alternative solution to overcome mind-wandering in relation to individual productivity by integrating theories from two disciplines, namely mindfulness theory in psychology and waqt and ridha theory in Sufism. The research method used is qualitative with the type of literature study. The data analysis technique used the hermeneutic method and the irfani method. The results of the study show that by being aware of the nature of waqt, ridha, and mindfulness, individuals will pay full attention to the task that is being done at that time. Regardless of whether the task is desirable or not, accepting all the thoughts, emotions, and bodily sensations that result from the experience without trying to change them will ultimately keep one’s mind from wandering anywhere and thereby increase productivity.